2011
DOI: 10.1161/circulationaha.110.952325
|View full text |Cite
|
Sign up to set email alerts
|

Deregulation of microRNA-503 Contributes to Diabetes Mellitus–Induced Impairment of Endothelial Function and Reparative Angiogenesis After Limb Ischemia

Abstract: Background-Diabetes mellitus impairs endothelial cell (EC) function and postischemic reparative neovascularization by molecular mechanisms that are not fully understood. microRNAs negatively regulate the expression of target genes mainly by interaction in their 3Ј untranslated region. Methods and Results-We found that microRNA-503 (miR-503) expression in ECs is upregulated in culture conditions mimicking diabetes mellitus (high D-glucose) and ischemia-associated starvation (low growth factors). Under normal cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
339
0
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 366 publications
(352 citation statements)
references
References 31 publications
(9 reference statements)
9
339
0
4
Order By: Relevance
“…A role of miRNAs in luteal angiogenesis is suggested by the finding that several of the miRNAs that were found to be differentially expressed between follicular and luteal tissues in ruminants (Fig. 3), including miR-125b, miR-145, mir-31, miR-503 and miR-21 (Cordes et al 2009, Caporali et al 2011, Muramatsu et al 2012, are known to regulate blood vessel formation. To precisely study the role of miRNAs in the CL, Otsuka et al (2008) used mice homozygous for a hypomorphic Dicer1 gene, which was associated with impaired luteal development and function leading to an inability to sustain pregnancy.…”
Section: Roles Of Mirnas During Luteal Developmentmentioning
confidence: 99%
“…A role of miRNAs in luteal angiogenesis is suggested by the finding that several of the miRNAs that were found to be differentially expressed between follicular and luteal tissues in ruminants (Fig. 3), including miR-125b, miR-145, mir-31, miR-503 and miR-21 (Cordes et al 2009, Caporali et al 2011, Muramatsu et al 2012, are known to regulate blood vessel formation. To precisely study the role of miRNAs in the CL, Otsuka et al (2008) used mice homozygous for a hypomorphic Dicer1 gene, which was associated with impaired luteal development and function leading to an inability to sustain pregnancy.…”
Section: Roles Of Mirnas During Luteal Developmentmentioning
confidence: 99%
“…As opposed to this, lentiviral-mediated expression of miR-503 in endothelial cells inhibited cell proliferation and migration. Expression of this microRNA was found to be upregulated in vascular endothelial cells growing in culture conditions mimicking diabetes mellitus (high glucose) and ischemia-associated starvation (low growth factors) (Caporali et al, 2011). These observations make miR-503 as a possible therapeutic target in diabetic patients with critical limb ischemia.…”
Section: Viral-based Deliverymentioning
confidence: 86%
“…In contrast, adenovirus-mediated overexpression of miR-98 in cardiomyocytes reduced cell size both at baseline and in response to angiotensin II suggesting for a protective role of this microRNA against angiotensin II-induced cardiac hypertrophy (Yang et al, 2011b). Caporali et al (2011) used an adenoviral vector to transfer a miR-503 decoy to the ischemic adductor of diabetic mice. The delivery of a miR-503 decoy corrected diabetes mellitus-induced impairment of post-ischemic angiogenesis and blood flow recovery.…”
Section: Viral-based Deliverymentioning
confidence: 99%
“…Weber et al (40) and Fleissner et al (41) also found that miR-21 was able to reduce the rate of apoptosis in vascular endothelial cells and promote the release of nitric oxide to protect the vascular endothelium. Caporali et al (42) reported that inhibition of miR-15 improved endothelial function in culture conditions mimicking diabetes mellitus (high D-glucose), and CCNE1 and CDC25A were direct miR-15 targets. The present study found that miR-93, miR-320 and miR-16 were highly expressed in the diabetic ED group, indicating that diabetic angiopathy played an important role in the onset of ED in patients with diabetes.…”
Section: Discussionmentioning
confidence: 99%